THE INFLUENCE OF BRAND AMBASSADOR JOE TASLIM AND TRUST IN SHOPEE INDONESIA’S PURCHASING DECISIONS - Mardhotilla Annisa Rahman; Awliya Afwa; Tubel Agusven (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The purpose of this study is to see if there is a significant influence between Brand Ambassadors, Trust in Purchasing Decisions in students of Riau Islamic University. The sample in this study was a student of Riau Islamic University who had worked at Shopee Indonesia and knew that one of Shopee Indonesia's Brand Ambassadors was Joe Taslim as many as 100 respondents with the Lemeshow formula (1997). The sampling technique in this study used Porpusive Sampling and Snowball Sampling Techniques. Methods for data processing using data collection scale techniques, Multiple Liner Regerence, Determination Efficiency, Partial T test, and simultaneous test F. From the results of the tests that have been carried out, it can be shown that the Brand Ambassador has a positive and significant effect on the purchase decision, Trust has a positive and significant effect on the purchase decision, and the Brand Ambassador and Trust have a positive and significant influence on the purchase decision.